Sensitivity Analysis and Simulation of TEG Dehydration Unit in Central Rumaila Compression Station in Basrah-Iraq - Khalaf, Ali Nasir (Basrah Journal for Engineering Sciences, 2017)
In the operating of TEG- dehydration unit in Central Rumaila Compression Station. Two operating parameters determine the efficient operating of the unit, the desired dew point depression and the losses of TEG. This work presents an attempt to study the effect of all the operating variables on the efficiency of the dehydration unit such as: the effect of pressure and temperature of the natural gas has to be treated on the water content. Contactor pressure, TEG circulating rate and stripping gas flow rate are also considered in this study. The results showed that decreasing the temperature of the absorber from 130 F to 120 F will reduce the mass fraction of water in the dry gas stream from 0.000076 to 0.00002. Increasing the absorber pressure from 549.7 psia (design pressure) to 600 psia will also reduce the water content in the outlet dry gas from 0.000076 to 0.000022 as mass fraction. The simulation result shows linear relation between the wet gas flow rate from the regeneration column and the lean glycol flow rate.